Chromium–Insulin Reduces Insulin Clearance and Enhances Insulin Signaling by Suppressing Hepatic Insulin-Degrading Enzyme and Proteasome Protein Expression in KKAy Mice - Wang, Zhong Q.; Yu, Yongmei; Zhang, Xian H.; Komorowski, James (Frontiers in Endocrinology, 2014)
JDS-CRI-003 (CRI) is a novel form of insulin that has been directly conjugated with chromium (Cr) instead of zinc. Our hypothesis was that CRI enhances insulin’s effects by altering insulin degrading enzyme (IDE) and proteasome enzymes. To test this hypothesis, we measured hepatic IDE content and proteasome parameters in a diabetic animal model. Male KKAy mice were randomly divided into three groups (n=8/group); Sham (saline), human insulin (Reg-In) and chromium conjugated human insulin (CRI), respectively. Interventions were initiated at doses of 2 U insulin/kg body weight daily for eight-weeks. Plasma glucose and insulin were measured. Hepatic IDE, proteasome and insulin signaling proteins were determined by western blotting. Insulin tolerance tests at week 7 showed that both insulin treatments significantly reduced glucose concentrations and increased insulin levels compared with the Sham group, CRI significantly reduced glucose at 4 and 6 hours relative to Reg-In (P<0.05), suggesting the effects of CRI on reducing glucose last longer than Reg-In. CRI treatment significantly increased hepatic IRS-1 and Akt1 and reduced IDE, 20S as well as 19S protein abundance (P<0.01, P<0.05, and P<0.001, respectively), but Reg-In only significantly increased Akt1 (P<0.05). Similar results were also observed in Reg-In and CRI treated HepG2 cells. This study, for the first time, demonstrates that CRI reduces plasma insulin clearance by inhibition of hepatic IDE protein expression and enhances insulin signaling as well as prevents degradation of IRS-1 and IRS-2 by suppressing ubiquitin-proteasome pathway in diabetic mice.